Buriad ajalguuny tolʹ - Gantogtoh, Gončigijn 1949- ("Bėmbi San" HHK, 2010)
Dictionary of the Buriat Mongol dialect
Includes bibliographical references (pages 18-22)
Keywords: Buriat language / Dialects / Dictionaries; Buriat language / Dictionaries / Mongolian; Buriat language / Dictionaries / Russian; Buriat language / Dialects / Mongolia; Buriat language; Buriat language / Dialects; Burjatisch; Mongolia; Wörterbuch